Dengue risk assessment - van Dodewaard, Caitlin A. (East Carolina University, 2015)
Dengue fever is the most prevalent vector borne disease in the world with over 3.6 billion people at risk and one billion new infections (including one million deaths) recorded annually. Risk assessments showing the impact of travel on the importation of dengue virus (DENV) are essential to understand the role of human travel in the spread of this mosquito-borne pathogen for which humans are the primary reservoir. Consequently, we calculated the exposure risk of United States (US) citizens traveling into Pan American countries where dengue (DEN) fever is endemic. The number of DEN cases in 51 Pan American countries was compared to the population of the same countries from 2001-2012 as a measure of exposure risk. Travel statistics (i.e. US travelers visiting the 51 Pan American countries) were analyzed and categorized by geographical region (i.e. North America, Central America, Andean, Southern Cone, Hispanic Caribbean and English, French and Dutch Caribbean). Travel patterns for US citizens were compared with subsequent DEN infections for each region visited. We show that US travelers visiting the Dominican Republic exhibited the highest number of imported DEN infections for the period of study. The Pan American country with the most DEN cases in its residents was Brazil (> 1 million reported cases in 2010). The numbers of DEN cases in Pan America continues to rise as does international travel and the geographic range of potential DENV vectors. Hence, in order for DENV risk assessments to improve, we must analyze possible routes of entry for this pathogen. There is also an increased risk of introducing new DENV serotypes into naïve human populations. Regions where all four DENV serotypes are prevalent are at the highest risk for DHF and DSS. Underreporting and misdiagnosis remains an issue for calculating DENV transmission risk and this is discussed. In the second part of this study, commercially available blood was analyzed for life table characteristics and vector competence. Commercially available blood can be used as an alternative to live animals to maintain mosquito colonies and deliver infectious blood meals during research studies. However, the extent to which artificially delivered blood sources affect mosquito life table characteristics of Aedes albopictus and vector competence for dengue virus (DENV) is unknown. Consequently, we analyzed the extent to which two blood sources affected life table characteristics (i.e. fecundity, fertility, hatch rate, adult survival) and vector competence (infection, dissemination, transmission) of Ae. albopictus for DENV. Two types of blood (N = 40 mosquitoes/group) were tested at two extrinsic incubation temperatures for DENV-infected and –uninfected mosquitoes as follows: 1) defibrinated, 27°C; 2) citrate, 27°C; 3) defibrinated, 30°C; 4) citrate, 30°C. Fully engorged mosquitoes were transferred to individual cages containing an oviposition cup and substrate. The presence of eggs was observed daily and, if eggs were observed, the substrate was removed and the number of eggs was counted (fecundity) for each female. Eggs were allowed to hatch and larvae were counted (fertility) for each female. At 14 and 21 days post feeding, 15 mosquitoes were taken from each group and tested for DENV in bodies (infection), legs (dissemination), and saliva (transmission). Mosquitoes fed DENV-infected defibrinated blood showed significantly higher DENV body titer (P = 0.034) and fecundity (P = 0.032), as well as faster hatch time (P = 0.039) compared to mosquitoes fed DENV-infected citrated blood. Temperatures tested here did not (P > 0.05) affect any factor measured. No differences were observed in DENV leg titers between treatments. DENV transmission was observed in all groups 14 days post infection and was observed in all but the 30°C defibrinated blood group at the 21 day post infection time point. Infected mosquitoes showed higher fecundity than uninfected mosquitoes (P = 0.001); however, fertility was lower in infected compared to uninfected mosquitoes (P = 0.001). Eggs of DENV-infected mosquitoes hatched faster than the uninfected groups (P = 0.005). We expect the findings of this study to improve methods for mosquito colony propagation and inform research using artificial blood delivery methods to assess vector competence.
Keywords: Environmental health; Entomology; Virology; Blood source; Extrinsic incubation temperature; Life table characteristics; Vector competence; Dengue; Travel--Health aspects; Travelers--United States; Risk assessment; Aedes albopictus